PENDIDIKAN KEWIRAUSAHAAN SEBAGAI VARIABEL MODERASI DALAM MEMBENTUK PERILAKU KEWIRAUSAHAAN : STUDI TEORI PERILAKU TERENCANA PADA USAHA MIKRO KECIL MENENGAH DI KOTA MEDAN - Simanihuruk, Peran; Tamba, Darwis; Simangunsong, Elisabeth; Sagala, Roslinda; Sinaga, Ria Veronica (UNIKA Santo Thomas, 2025)
This study aims to analyze the moderating role of entrepreneurship education on entrepreneurial behavior based on the Theory of Planned Behavior (TPB) among 400 MSME actors in Medan City. The data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach via SmartPLS version 4. The results show that entrepreneurship education significantly moderates the influence of attitude and perceived behavioral control on entrepreneurial behavior, but does not moderate subjective norms and entrepreneurial intention. These findings highlight the importance of entrepreneurship education programs that focus on shaping positive attitudes and enhancing self-control perceptions to foster entrepreneurial behavior among MSMEs. The government and related institutions are advised to develop sustainable mentoring programs and access to capital as tangible support for MSME actors, while the entrepreneurs themselves are encouraged to actively participate in entrepreneurship training to enhance business capacity and competitiveness amid market dynamics. This study is limited to the Medan City area and relies on subjective perception data; therefore, future research is recommended to expand the geographical scope and adopt qualitative methods for deeper understanding.